JRDM 2019
DOI: 10.7176/jrdm/57-04
|View full text |Cite
|
Sign up to set email alerts
|

Employee and Organizational Performance: Impact of Employee Internal and External Factors, Moderated by Online Application

Abstract: The purpose of this study is analyze the internal factors impact of an employee (especially age, discipline, and motivation), and external factors of employee (especially training and incentives) on employee performance and organizational performance. The moderation impact of online application also analized at the relationship between employee performance on organizational performance. Used taxi drivers as unit analysis is an uniqueness of this study, the snowballing method with e-questionnaire used for colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Lai et al (2020) also indicated that transformational leadership increased job performance. According to Tarmidi and Arsjah (2019), job performance was positively related to the organizational performance. Finally, Al Khajeh (2018) stated that it was beneficial to organizational performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lai et al (2020) also indicated that transformational leadership increased job performance. According to Tarmidi and Arsjah (2019), job performance was positively related to the organizational performance. Finally, Al Khajeh (2018) stated that it was beneficial to organizational performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although their research was not strictly concerned with family firms, Kim et al (2017) offered interesting findings that suggested that organizational identification was positively related to a company's financial performance. Furthermore, the research conducted among employees from the hotel industry showed that there was a positive relationship between organizational identification and job performance (Demir et al, 2014) which is beneficial to the concept of organizational performance (Tarmidi and Arsjah, 2019).…”
Section: Sew and Family Firm's Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Ini terjadi karena Google LLC memberlakukan sistem baru (Victor, 2022). Kinerja perusahaan dapat terganggu jika keadaan seperti ini diabaikan (Tarmidi et al, 2019). Secara langsung, dampak dari kinerja karyawan yang buruk adalah biaya mahal yang perlu dikeluarkan perusahaan untuk membayar karyawan-karyawan dengan kinerja buruk tersebut (Moskowitz, 2012), rotasi karyawan yang tinggi, moral rendah karyawan, menyia-nyiakan sumber daya, karyawan yang kehilangan motivasi, beresiko terkena masalah terkait hukum, tingkat kesehatan karyawan yang rendah, serta berkurangnya produktivitas (Zambas, 2022).…”
Section: Pendahuluanunclassified
“…al (2022), employee performance is the most important indicator of a company's capacity to fulfil its goals, and each employee must contribute to the company's vision and purpose. A study conducted by Tarmidi and Arsjah (2019) found in their study that employee performance has a positive impact on organisational performance directly and indirectly. Thus, it is crucial to ensure that the employees perform significantly to ensure the success of an organisation.…”
Section: Introductionmentioning
confidence: 97%